Influence of internet, mobile phone use, and sociodemographic factors on women’s knowledge and attitude towards contraception in Indonesia - Achmad Kemal Harzif; Amalia Shadrina; Edward Christopher Yo; Nia Reviani; Andon Hestiantoro (Obstetrics & Gynecology Science, 2023)
Objective Rapid population growth has been a problem in Indonesia for several decades. One of the reasons for this phenomenon is limited knowledge of reproductive health and proper contraception methods. The use of mobile phones and the internet has made it easier to access health information. This study aimed to determine the influence of the internet, mobile phone use, and sociodemographic factors on Indonesian women’s knowledge of and attitudes toward contraception. Methods The present study used secondary data from the 2017 Indonesian Health and Demographics Survey. Altogether, 49,627 women participated in this study. Descriptive statistics were performed, and bivariate analysis using the chi-squared test was performed to measure the association between variables. Results Knowledge about the ovulation cycle and contraception was positively associated with mobile phone ownership, frequent internet use, higher wealth index, reading printed media, listening to the radio, watching the television, higher educational level, and older age. The use and intention of contraception were positively associated with lower wealth index, watching television at least once a week, primary-secondary educational level, rural residence, and older age. Thus, acquisition of knowledge does not necessarily translate into implementation of contraceptive methods, since there might be certain digital and social barriers. Conclusion Access to the internet and mobile phones as well as certain sociodemographic factors have contributed to an increase in women’s knowledge about contraception, but not necessarily in their knowledge regarding the use of contraception.